Oral low dose of glutamine improved the spontaneous closure in patients with external duodenal fistula: a retrospective comparative study with propensity score matching - Huang, Ming; Luo, Shikun; Yao, Zheng; Xu, Xin; Zhao, Risheng; Zhao, Yunzhao; Yu, Tianchi (Frontiers in Nutrition, 2025)
BackgroundSpontaneous closure of external duodenal fistula (EDF) is associated with reduced gastrointestinal inflammation. Low-dose glutamine supplementation in the intestine can directly improve intestinal permeability and promote mucosal healing, potentially aiding fistula closure. This study investigates the effects of oral glutamine supplementation on EDF treatment outcomes.MethodsA retrospective cohort study was conducted from January 2019 to June 2024, including 104 adult patients with EDF. Based on the administration of low-dose (10 g/day) oral glutamine supplementation, patients were divided into a glutamine group (n = 54) and a non-glutamine group (n = 50), with 46 matched pairs after propensity score matching (PSM). The outcomes were spontaneous fistula closure, mucosal healing, and hospital stay duration.ResultsSpontaneous closure occurred in 28 patients (52%) in the glutamine group, compared to 21 patients (42%) in the non-glutamine group (p = 0.04). Glutamine promoted fistula closure both before (HR = 1.82; 95% CI: 1.03–3.23, p = 0.04) and after PSM (HR = 1.94; 95% CI: 1.07–3.53, p = 0.03). The median hospital stay was shorter in the glutamine group, both before [65 days (IQR: 32–121 days) vs. 106 days (IQR: 56–119 days), p = 0.01] and after PSM [76 days (IQR: 32–122 days) vs. 110 days (IQR: 54–122 days), p = 0.02].ConclusionGlutamine supplementation may enhance spontaneous EDF closure and reduce hospital stay duration.